The roles of energy markets and environmental regulation in reducing coal‐fired plant profits and electricity sector emissions. (12th September 2019) - Linn, Joshua; McCormack, Kristen
Abstract: Between 2005 and 2015, US electricity sector emissions of nitrogen oxides and sulfur dioxide, which harm human health and the environment, declined by two thirds, and many coal‐fired power plants became unprofitable and retired. Intense public controversy has focused on these changes, but the literature has not identified their underlying causes. Using a new electricity sector model of the US eastern interconnection that accurately reproduces unit operation, emissions, and retirement, we find that electricity consumption and natural gas prices account for nearly all the coal plant profitability declines and resulting retirements. Environmental regulations had little effect on these outcomes.